Feasibility of the use of Lentinula edodes mycelium in terbinafine remediation - Kryczyk-Poprawa, Agata; Piotrowska, Joanna; Żmudzki, Paweł; Opoka, Włodzimierz; Muszyńska, Bożena (3 Biotech, 2020)
A detailed understanding of the fate of xenobiotics introduced into the environment and the mechanisms involved in their biotransformation, biodegradation, and biosorption is essential to improve the efficiency of remediation techniques. Mycoremediation is a form of bioremediation technique that has become increasingly popular in recent years as fungi are known to produce various effective extracellular enzymes that have the potential to neutralize a wide variety of xenobiotics released into the environment. Hence, mycoremediation appears to be a promising technique for the removal of a wide array of toxins and pharmaceutical residues from a damaged environment and wastewater. This study primarily aimed to investigate whether white-rot fungus ( Lentinula edodes ) can be utilized for the bioremediation of common antifungal agent terbinafine, which is mainly available in the market as powder or cream. The cultures of L. edodes were cultivated in the medium containing terbinafine powder or terbinafine 1% cream, each at a final concentration of 0.1 mg mL −1 . The addition of terbinafine in powder form have a negative effect on biomass growth ( p < 0.05). The total amount of terbinafine in the dry weight of mycelium after culture was estimated to be 7.63 ± 0.45 mg and 12.52 ± 2.46 mg for powder and cream samples, respectively. In addition, there were no traces of terbinafine in any of the samples of medium used for culturing L. edodes after the experimental duration period. The biodegradation products of terbinafine were identified for the first time using UPLC/MS/MS. The biodegradation of terbinafine resulted in the loss of 1-naphthylmethanol, which occurred via oxidative deamination, N -demethylation, or tert-butyl group hydroxylation. The results of the study demonstrate that L. edodes mycelium can be effectively used for the remediation of terbinafine.